Densidades de siembra y su efecto en el rendimiento del cultivo ají pimentón (capsicum annuum L), en la – banda de shilcayo-San Martín-Perú - Gamarra Pérez, César Augusto (2008)
This thesis work entitled "Planting densities and its Effect on Crop Yield of Pepper Pepper (Capsicum annuum L), in the - Band Shilcayo - San Martin • Peru" Aims to compare the performance of the chili pepper, California wonder variety, in different densities in the Fundo miraflores, Ahuashiyacu sector, destrito of the band Shilcayo. likewise do the economic analysis of all treatments evaluated. The experimental design used in this work, was a design of randomized blocks with five (5) treatments and tour (4) repetitions. The parameters were to assess plant height, number of fruit per plant, average fruit size, weight of fruit-harvest treatment and performance expressed in MT I Ha, of which treatments T3 (70 x 50 cm) and T4 (70 x 60 cm), had the best results were obtained in terms of number of fruit per plant, length and breadth of fruits and productiQn. This research was carried out in the Fundo Miraflores located 3.5 kilometers from Tarapoto, Ahuashiyacu sector, the Banda district of Shilcayo owned by the Universidad Nacional de San Martín Tarapoto. In relation to the Cost I Benefit, treatments T4 (70 x 64 cm) and T3 (70 x 50 cm), were the most income received with respect to other treatments, with a cost / benefit (12.01) and a net profit of S l. 63129.58 for T4 and a cost / benefit of (11.85); with a net profit of S l. 67241.61 for the T3, T5, taking the cheapest with a cost I benefit ratio (6.36) anda net profit of S /. 32128.46 respectively.